The study of leptin concentration in saliva during orthodontic treatment, periodontal diseases and wound healing in the oral mucosa-review - Cwalina, Izabela; Komarowska, Marta; Dargiewicz, Ewelina; Hermanowicz, Adam (Journal of Education, Health and Sport, 2018)
BackgroundThe oral cavity is a very complex environment characterized by numerous interactions between different tissues, secretions from various glands, foods, air and microorganisms. Leptin is a hormone-like protein, which plays an important role in protection of host against inflammation and infection. It exhibits many physiological properties. Some studies have reported changes in leptin levels during orthodontic treatment, wound healing, periodontal disease. The aim of the paper was to review the salivary leptin role in each of these cases.MethodsArticles published before November 2018 were obtained from PubMed, Dentistry & Oral Sciences Source. Inclusion criteria were: a) empirically based b) peer-reviewed. Discussion and resultsSalivary leptin levels significantly decrease during orthodontic tooth movement and periodontal diseases. However, it increases while wound healing in the oral mucosa.ConclusionThere is a correlation between tooth movement and leptin level. Obese patients could have lesser tooth movement. This hormone promotes wound healing and angiogenesis in oral cavity. Leptin concentration in saliva increases in patients with periodontitis.